2009
DOI: 10.2174/157016209788680598
|View full text |Cite
|
Sign up to set email alerts
|

Medication Assisted Treatment in the Treatment of Drug Abuse and Dependence in HIV/AIDS Infected Drug Users

Abstract: Drug use and HIV/AIDS are global public health issues. The World Health Organization (WHO) estimates that up to 30% of HIV infections are related to drug use and associated behaviors. The intersection, of the twin epidemics of HIV and drug/alcohol use, results in difficult medical management issues for the health care providers and researchers who work in the expanding global HIV prevention and treatment fields. Access to care and treatment, medication adherence to multiple therapeutic regimens, and concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 92 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have indicated that HIV-positive IDUs experience comparatively low rates of access and adherence to HIV treatment, and consequently this population has not benefited from modern HIV treatments to the same extent that other HIV-affected populations have (Kresina, Bruce, & McCance-Katz, 2009; Wood et al, 2003). Given that the SIF in Vancouver is attracting high-risk IDUs with a lower likelihood of receiving HIV treatment, the SIF could provide a venue for enhanced HIV care, including viral load and CD4 count testing, vaccinations and other preventive measures, and distribution of antiretroviral therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that HIV-positive IDUs experience comparatively low rates of access and adherence to HIV treatment, and consequently this population has not benefited from modern HIV treatments to the same extent that other HIV-affected populations have (Kresina, Bruce, & McCance-Katz, 2009; Wood et al, 2003). Given that the SIF in Vancouver is attracting high-risk IDUs with a lower likelihood of receiving HIV treatment, the SIF could provide a venue for enhanced HIV care, including viral load and CD4 count testing, vaccinations and other preventive measures, and distribution of antiretroviral therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid substitution therapy (OST), in particular methadone maintenance therapy (MMT) and buprenorphine-naloxone (BUP), has been shown to be effective in reducing opioid use, preventing relapse, and enhancing ART and HIV treatment adherence among people with HIV/AIDS [66][67][68]. Recent work suggests that the context and delivery of OST may affect HIV treatment attendance and drug use cessation rates.…”
Section: Heroinmentioning
confidence: 99%
“…Substance use in HIV-infected patients has been linked to poor ART adherence, low access to care, low health-related quality of life, and impairment of physical and mental health (Korthuis et al, 2008;Kresina, Bruce, & McCance-Katz, 2009;Lima et al, 2014;).…”
Section: Introductionmentioning
confidence: 99%